Differences in postoperative maladaptive behavioral changes between partial and total tonsillectomy patients. (March 2018) - Cai, Yi; Lopata, Lindsay; Dodhia, Sonam; Monteleone, Matthew; Haddad, Joseph; Sun, Lena S.
Abstract: Introduction: Behavioral difficulties associated with sleep-disordered breathing (SDB) improve after tonsillectomy, but surgery may lead to the development of short-term postoperative maladaptive behavioral changes (PMBCs). These PMBCs have not been compared between total and partial tonsillectomy patients. Methods: SDB patients aged 1–6 years undergoing tonsillectomy were recruited. Parent phone surveys were conducted at 48–72 hours and 1–2 weeks postoperatively. Parents identified PMBCs using the Post-Hospital Behavior Questionnaire (PHBQ), scoring changes in behavior compared to baseline. PMBCs were defined by PHBQ scores >0 and compared by one-tailed t -test. Postoperative pain was categorized as mild, moderate, and severe pain using the Parents' Postoperative Pain Measure (PPPM). Differences in pain levels were analyzed by Chi-squared test. A p-value <0.05 was deemed statistically significant. Results: Seventy-eight children completed the study, with 29 total tonsillectomy and 49 partial tonsillectomy patients. At both time points after surgery, PHBQ scores were higher in total tonsillectomy patients than in partial tonsillectomy patients (3.41 ± 3.53 versus 1.94 ± 2.25 at 2–3 days, p = .013). PMBCs were also more frequent in total than partial tonsillectomy patients (76% versus 59% at 2–3 days; 28% versus 7% at 1–2 weeks). Meanwhile, distribution of pain levels was similar between both partial and total tonsillectomy patients. Conclusions: Our study indicates that total tonsillectomy patients more frequently experience PMBCs than do partial tonsillectomy patients despite similar distributions in pain levels postoperatively. This difference in PHBQ scores between total and partial tonsillectomy patients should be further explored.